Komunikasi Politik Kyai dalam Pengembangan Pesantren (Studi Analisis Terhadap Pondok Pesantren Sunan Drajat Lamongan) - Hadi Ismanto (Universitas Sunan Drajat Lamongan, Indonesia, 2023)
Kyai is a very interesting figure in Islam. His charisma is huge in the eyes of the public. Kyai influence in almost all fields. The magnitude of this influence makes many political actors, structural officials, businessmen and Muslims who are in the social environment of the kyai. So often, state officials approach the kyai for the sake of harmonization of the government's development policies. It is from here that the kyai get feedback in the form of resources that can be transformed into the internal of the Islamic boarding schools as initial capital for the development of the pesantren. To make it happen, the kyai do it with a political communication approach to all the ranks under him. This study was directed at the Sunan Drajat Islamic Boarding School, Lamongan, East Java by analyzing and describing field findings. Research subjects were selected based on purposive testing. Kyai who are the subject of this research are those who are actively involved in developing pesantren. The consequences of this study show that political communication carried out by kyai can synergize leadership policies in each institution and is able to accelerate the development of Islamic boarding schools in a better direction. This shows that the existence of kyai cannot be separated from efforts to develop Islamic boarding schools.